Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T17:04:11+01:00
A) x= -2x-1+7
x+2x=-1+7
3x=6/ :3
x=2
y=-2×2-1
y=-4-1
y=-5
x=2
y=-5
b
4a-2b=10/×(-1)
5a-2b=10
-4a+2b=-10
5a-2b=10
a=0
4×0-2b=10
-2b=10/:(-2)
b=-5
a=0
b=-5
c)4(x-2)-(y-2)=1
10x-2y=18
4x-8-y+2=1/×(-2)
10x-2y=18
-8x+16+2y-4=-2
10x-2y=18
-8x+2y=-2-12
10x-2y=18
-8x+2y=-14
10x-2y=18
2x=4/:2
x=2
10×2-2y=18
20-2y=18
-2y=18-20
-2y=-2/:(-2)
y=1
x=2
y=1
d
2x-4(y+1)=10
2(x+3)-(1-y)=9
2x-4y-4=10/×(-1)
2x+6-1+y=9
-2x+4y+4=-10
2x+6-1+y=9
-2x+4y=-10-4
2x+y=9-5
-2x+4y=-14
2x+y=4
5y=-10/:5
y=-2
2x-2=4
2x=4+2
2x=6/:2
x=3
y=-2